"We need to 'shake' the bill to make sure it works for patients". (14th March 2011) - Coombes, Rebecca
Abstract : Last week the BMJ brought together a group of influential clinicians and thinkers in UK healthcare to discuss the radical changes afoot in the NHS. Rebecca Coombes summarises the key points. You can also listen to edited highlights in a BMJ podcast (www.bmj.com/podcasts )